Analysis of scaling relationships for flood parameters and peak discharge estimation in tropical regions data - Grabowski, Robert C. (Cranfield University, 2024)
Hydrological data from the La Sierra catchment (Mexico), including input data used in the statistical modelling and output data from the scaling, correlation and regression analyses. Please see the readME file for the list of data and the published paper for more information
Keywords: Flood Forecasting'; 'Statistical Model'; 'rainfall events'; 'flood warning system'; 'Flood wave'